Respuesta :

Answer:

x = 2

y = 3

Step-by-step explanation:

y = 2x – 1

y - 2x = -1

y = 5x – 7

y - 5x = -7

y - 2x = -1

y - 5x = -7

_________--

3x = 6

x = 6/3

x = 2

y = 2x – 1

y = 2(2) - 1

y = 4 - 1

y = 3

[tex]x=2\\y=3[/tex]

Substitution method:

  • The substitution method is one approach to take into consideration.
  • When one equation with one variable is solved, this expression is then used in the other equation.
  • The substitution method entails solving for a single variable before inserting the solution into the other equation.

Elimination method:

  • To create an equation in one variable using the elimination approach, you can either add or subtract the equations.
  • To eliminate a variable, add the equations when the coefficients of one variable are in opposition, and subtract the equations when the coefficients of one variable are inequality.

Solution - (Through substitution method)

Given -

[tex]y=2x-1\\y=5x-7[/tex]

So, substitute [tex]y=2x-1[/tex] in [tex]y=5x-7[/tex].

[tex]y=5x-7\\2x-1=5x-7\\5x-2x-7+1=0\\3x-6=0\\3x=6\\x=\frac{6}{3} \\x=2[/tex]

Now, substitute [tex]x=2[/tex] in [tex]y=2x-1[/tex].

[tex]y=2x-1\\y=2(2)-1\\y=4-1\\y=3[/tex]

Therefore, [tex]x=2[/tex] and [tex]y=3[/tex].

Know more about the substitution method here:

https://brainly.com/question/22340165

#SPJ2

ACCESS MORE